Immobilised Chlorella vulgaris as An Alternative for The Enhancement of Microalgae Oil and Biodiesel Production - Nur Hanani Rushan; Nur Hidayah Mat Yasin; Farhan Mohd Said; Nagaarasan Ramesh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Microalgae are a promising alternative for biodiesel production and a valuable source of fatty acid methyl ester (FAME). In this research, Chlorella vulgaris has been chosen as the suitable microalgae because this species was able to produce highest oils for biodiesel processing. Previously, sodium alginate (SA) was used to entrap the microalgae in the culturing process due to its low toxicity and high transparency. However, SA have some disadvantages such as bead disruption which leading to the loss of microalgae cell. Therefore, this research has been conducted to evaluate the oil production of immobilised Chlorella vulgaris using different matric systems at different ratios which are 0.3:1, 1:1 and 2:1. Currently, six matric systems have been developed, they are SA as a control, a combination of SA and chitosan (SA+CT), SA and carrageenan (SA+CR), SA and gelatin (SA+GT), SA and calcium alginate (SA+CA), and SA and sodium carboxymethylcellulose (SA+CMC). The microalgae was first cultivated, harvested and extracted to produce oil, prior to use in the transesterification process. The SA+GT showed the highest oil yield with 59.14% and a total FAME of 0.56 mg/g. The FAME profile of oil extracted microalgae showed high potential for biodiesel production as it consisted of palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1), linoleic acid (C18:2) and linolenic acid (C18:3). The results proved that the combination of SA+GT had improved the oil yield and fatty acid composition as compared to the other matric systems, which may have useful application for the biodiesel industry. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).